PERENCANAAN ULANG TRAFFIC LIGHT PADA SIMPANG PRESIDEN KOTA PADANG - Bayu Budi Irawan (LPPM Universitas Abdurrab, 2020)
In 2019 the presidential intersection was renovated by installing traffic lights, increasing the number of lanes, and geometric changes to the Jhoni Anwar road arm. The redesign is done by widening the road on the Jhoni Anwar (T) arm from 6.5 m to 9 m and the application turns left following the Traffic Light (PLT) on the arm of Jhoni Anwar (B). The recalculation results obtained a DS value of 0.83 with a service level